Histoplasma capsulatum presenting as generalized lymphadenopathy after renal transplantation() - Saucedo-Crespo, Hector (IDCases, 2020)
Histoplasma capsulatum is typically an indolent disease among immunocompetent patients. However, immunocompromised patients, such as solid organ transplant recipients, are at risk of developing severe histoplasmosis. Yet post-transplant histoplasmosis is a rare pathology, representing less than five percent of invasive fungal infections among transplant recipients. Furthermore, patients tend to present with nonspecific clinical symptoms, complicating timely diagnosis and delaying treatment. Disease features that may be more representative of H. capsulatum infection, such as anemia, leukopenia and pulmonary involvement are often not present until late in the disease course, when the patient is at greater risk of decompensation. Unlike H. capsulatum infections among immunocompetent hosts, extrapulmonary infection among immunocompromised hosts is more the rule than the exception. Treatment with liposomal amphotericin B followed by oral itraconazole is the standard therapy, but special considerations must be made for patients with hepatic and/or renal insufficiency, underlying cardiac abnormalities or malabsorptive pathologies and doses of immunosuppressants will need to be adjusted for drug interactions. Herein we present a case of H. capsulatum infection presenting with generalized lymphadenopathy post-renal transplant.